Pemanfaatan Media Pembelajaran Online di SMA Negeri 2 Lais pada Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan - Hudalana, Hudalana; Wardiah, Dessy; Riyoko, Endie (Indonesian Research Journal on Education, 2022)
The purpose of this study was to determine the use of online learning media at SMA Negeri 2 Laisin the subjects of physical education, sports and health.The type of research and the method usedis a qualitative method. The object in this study is the "Principal" and the informants in this studyare PJOK teachers and students at SMA Negeri 2 Lais. The data collection techniques were carried out by means of observation, interviews and documentation. The data analysis techniqueused is data reduction and data presentation. The results of this study are the use of online learning media at SMA Negeri 2 Lais in the form of WhatsApp as a learning medium for sportsand health physical education. learning activities that contain learning activities in the form ofmaterials, collection of assignments and as a medium of interaction between teachers andstudents. Then the features that are often used are photos, videos, documents, WhatsApp groups,and direct calls. Ease is felt with the presence of the WhatsApp feature and also its easy use andcan be used by various groups. The use of media by students during online learning is in the formof WhatsApp to send assignments and receive physical education, sports and health lessons and to interact with teachers and other students.